Wavelength Scaling of Photoionization of Size-Dependent Dielectric Nanoparticles - Powell, J.; Summers, A.; Kling, Matthias F.; Rolles, D.; Trallero-Herrero, C.; Rudenko, A. (Conference Proceedings - Lasers and Electro-Optics Society Annual Meeting-LEOS, 2020)
We present the effects of wavelength scaling on the photoelectron cutoff energy of laser-driven dielectric nanoparticles. Results indicate a complex mix of ponderomotive scaling, field enhancement and charge interactions dictate photoionization and subsequent electron propagation.
CRIS-Team Scopus Importer:2023-04-20